DECOMPRESSIVE HEMICRANIECTOMY AFTER UNSUCCESSFUL INTRAVENOUS THROMBOLYSIS OF MALIGNANT MIDDLE CEREBRAL ARTERY INFARCTION: A CASE REPORT - S.M. SEHWEIL (Avicenna Tajik State Medical University, 2023)
Objective: The gold standard treatment for patients with cerebral infarction (CI) is intravenous thrombolysis, and it is superior to standard therapy in improving functional status. Malignant middle cerebral artery infarction (MMCAI) is characterized by ischemic injury of 50% or more of the territory supplied by MCA, which, in turn, is a contraindication to thrombolytic therapy. When patients are admitted to the hospital within the therapeutic window before identification of a hypodense lesion by computed tomography, detecting the MMCAI promptly is challenging. Consequently, these patients receive intravenous thrombolysis. The article describes a successful decompressive hemicraniectomy (DHC) in a patient with MMCAI following ineffective, uncomplicated intravenous thrombolysis.